A versatile phosphorothioate bearing benzimidazole for the preparation of flame retardant, mechanically strong and high transparency epoxy resins. (September 2022) - He, Ling-Xiang; Liu, Xin-Duo; Zheng, Xian-Ting; Dong, Ying-Qi; Bai, Wei-Bin; Lin, Yu-Cai; Jian, Rong-Kun
Highlights: A versatile phosphorothioate bearing benzimidazole ring (DP-MBI) was synthesized. EP with 3 wt% DP-MBI passed a V-0 rating and achieved the LOI value of 32.6%. DP-MBI modified EP presented strengthened mechanical properties. DP-MBI offered the modified EP high transparency. Abstract: Integrating excellent flame retardancy, robust mechanical properties and high transparency into epoxy resin (EP) still remains challenging using available flame retardants at a super-low loading. S-benzimidazolyl diphenylphosphorothioate (DP-MBI) has been synthesized in an attempt to address this deficiency. The flammability of EP may be greatly diminished through incorporation of only 3 wt% DP-MBI. The resultant EP blend is self-extinguishing, displaying a V-0 rating and a LOI value of 32.6%. The release of heat and smoke during combustion is lower than those observed for combustion of pure EP. The improvement in flame retardancy is ascribed to the cooperation of phosphorus, nitrogen and sulfur moieties mainly in the gaseous phase. Moreover, by virtue of the incorporation of DP-MBI into the mainchain of epoxy macromolecules, the flexural and impact strength for an EP blend containing 3 wt% DP-MBI increased from 104.7 MPa and 31.1 kJ/m 2 for pure EP to 111.2 MPa and 37.1 kJ/m 2, respectively. Additionally, besides a good ultraviolet shielding effect, the transparency of the modified EP is 100% of that for pure EP. Generally, a versatile flame retardant for epoxy resins, effective at a super-low loading, with promising potential industrial promising application has been prepared.